A Simple Method for Evaluating the Bioactive Phenolic Compounds’ Presence in Brazilian Craft Beers - Marcelo Coelho Silva; Jeancarlo Pereira dos Anjos; Lilian Lefol Nani Guarieiro; Bruna A. Souza Machado (Molecules, 2021)
There are a significant number of analytical methodologies employing different techniques to determine phenolic compounds in beverages. However, these methods employ long sample preparation processes and great time consumption. The aim of this paper was the development of a simple method for evaluating the phenolic compounds’ presence in Brazilian craft beers without a previous extraction step. Catechin, caffeic acid, epicatechin, p-coumaric acid, hydrated rutin, trans-ferulic acid, quercetin, kaempferol, and formononetin were analyzed in fifteen different craft beers. The method showed good linearity (R2 ≥ 0.9966). The limit of detection ranged from 0.08 to 0.83 mg L−1, and limits of quantification were between 0.27 and 2.78 mg L−1. The method showed a satisfactory precision (RSD ≤ 16.2%). A good accuracy was obtained by the proposed method for all phenolic compounds in craft beer (68.6% ˂ accuracy ˂ 112%). Catechin showed higher concentrations (up to 124.8 mg L−1) in the samples, followed by epicatechin (up to 51.1 mg L−1) and caffeic acid (up to 8.13 mg L−1). Rutin and formononetin were observed in all analyzed samples (0.52 mg L−1 to 2.40 mg L−1), and kaempferol was less present in the samples. The presence of plant origin products was determinant for the occurrence of the highest concentrations of phenolic compounds in Brazilian craft beers.